A hollow fiber nitrogen-rich separation membrane and its preparation method and application

By optimizing the composition of the cast film liquid, selecting a specific ratio of polysulfone and sulfonated polysulfone, and adding nanofibers, a hollow fiber nitrogen-rich separation membrane is prepared, which solves the problem that existing membranes are difficult to take into account gas permeability, mechanical strength and pressure resistance, and achieves efficient oxygen-nitrogen separation and commercial application.

CN118526990BActive Publication Date: 2025-04-08TSINGHUA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410709426.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-04-08
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

The existing hollow fiber nitrogen-rich separation membranes are difficult to take into account both gas permeability, mechanical strength and pressure resistance. They have problems such as high permeability and high selectivity and poor uniformity, which limits large-scale commercial applications.

Method used

By optimizing the composition of the cast film liquid, select a specific ratio of polysulfone and sulfonated polysulfone, and add nanofibers, such as Kevlar fiber, cotton fiber, carbon fiber, etc., to prepare a hollow fiber nitrogen-rich separation membrane. This method improves the mechanical strength of the film and the bendability during processing while maintaining permeability.

Benefits of technology

The hollow fiber nitrogen-rich separation membrane has the advantages of high mechanical strength, good breathability and high pressure resistance. It has good permeability and selectivity for the oxygen/nitrogen separation process, and has promoted the commercial application of the hollow fiber nitrogen-rich separation membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004873576040000121
    Figure BDA0004873576040000121
  • Figure HDA0004873576050000011
    Figure HDA0004873576050000011
Patent Text Reader

Abstract

The present invention provides a hollow fiber nitrogen-rich separation membrane and a preparation method and application thereof. The casting liquid of the hollow fiber nitrogen-rich separation membrane includes a liquid phase component and a solid phase component. The solid phase component includes an organic polymer, a pore former and nanofibers; the organic polymer is composed of polysulfone and sulfonated polysulfone in a mass ratio of 5 to 20:1; the mass proportion of the pore former in the solid phase component is 0.1% to 0.5%; the mass proportion of the nanofiber in the solid phase component is 5% to 15%. The hollow fiber nitrogen-rich separation membrane prepared by the present invention through the reasonable combination of the casting liquid components has the advantages of high mechanical strength, good air permeability and high pressure resistance, and has good permeability and selectivity when used in the oxygen / nitrogen separation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of gas separation membranes, and in particular to a hollow fiber nitrogen-rich separation membrane and a preparation method and application thereof. Background Art

[0002] Membrane separation technology has the advantages of no phase change, low energy consumption, and safe operation. It is a green and sustainable development technology with broad application prospects.

[0003] Hollow fiber gas separation membrane is a highly efficient gas separation technology that uses special membrane materials and structural design to achieve selective separation of different gas molecules. This membrane is characterized by a hollow fiber structure that can separate different gases according to the size and properties of gas molecules under a certain pressure difference. Hollow fiber gas separation membrane has the advantages of simple production process and high packing density, and is the main research direction of commercial gas separation membranes. Among them, hollow fiber nitrogen-rich separation membranes are widely used in important national fields such as petrochemicals, engines, coal mines, and medical care.

[0004] Generally, hollow fiber nitrogen-rich separation membranes are required to have gas permeability, mechanical strength, pressure resistance and other performances. Among them, gas permeability refers to the high oxygen permeability and low nitrogen permeability of the hollow fiber membrane, so as to have a certain oxygen-nitrogen separation ratio; the mechanical strength is required so that the membrane can withstand mechanical operations such as bending and friction during the assembly process; the hollow fiber membrane is required to have pressure resistance because the membrane needs to operate in a high-pressure environment in actual working conditions, so the stability of the membrane under high pressure is also extremely important.

[0005] Although the prior art has proposed some hollow fiber nitrogen-rich separation membranes, it is difficult to take into account the performance of the above-mentioned aspects at the same time. There are problems such as high permeability and high selectivity cannot be achieved at the same time and poor uniformity, so large-scale commercialization is limited. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a hollow fiber nitrogen-rich separation membrane and a preparation method and application thereof.

[0007] In a first aspect, the present invention provides a hollow fiber nitrogen-rich separation membrane, wherein the casting liquid of the hollow fiber nitrogen-rich separation membrane comprises a liquid phase component and a solid phase component, wherein the solid phase component comprises an organic polymer, a pore-forming agent and nanofibers; the organic polymer is composed of polysulfone and sulfonated polysulfone in a mass ratio of 5 to 20:1; the mass proportion of the pore-forming agent in the solid phase component is 0.1% to 0.5%; the mass proportion of the nanofiber in the solid phase component is 5% to 15%.

[0008] The composition of the casting solution of the hollow fiber nitrogen-enriched separation membrane is a key factor in the preparation process, which directly affects the performance and structure of the final membrane. The casting solution is usually composed of a polymer, a solvent (liquid phase component), a pore-forming agent and other optional additives, and the selection and proportion of these components are crucial to the formation of the membrane. Among them, the polymer is the main component of the casting solution, and the selection of the polymer determines the chemical properties and basic mechanical strength of the membrane. The present invention finds that the polymer selection of polysulfone and sulfonated polysulfone composed of a specific ratio is helpful to enrich nitrogen. At the same time, the present invention adds nanofibers, which help to improve the mechanical strength of the membrane while maintaining permeability, and has strong bendability during processing.

[0009] In some embodiments of the present invention, the nanofiber is selected from one or more of Kevlar fiber, cotton fiber, carbon fiber, and cellulose.

[0010] Preferably, the diameter of the nanofiber is D, and the length is L, which respectively satisfy: 5nm≤D≤50nm, 500nm≤L≤5000nm.

[0011] Further preferably, the diameter D and length L of the nanofiber also satisfy: 100≤L / D≤200.

[0012] In a preferred embodiment of the present invention, the number average molecular weight Mw of the polysulfone is 50,000 to 80,000;

[0013] The number average molecular weight Mw of the sulfonated polysulfone is 50,000 to 80,000, and the sulfonation degree is 10 to 30%.

[0014] In some embodiments of the present invention, the pore-forming agent is selected from one or more of polyethylene glycol and polyvinyl pyrrolidone.

[0015] In some embodiments of the present invention, the liquid phase component is a mixture of one or more of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and water. Preferably, the mass ratio of one or more of N,N-dimethylacetamide, N,N-dimethylformamide and dimethyl sulfoxide to water is 10 to 20:1.

[0016] The choice of solvent (liquid phase component) has a significant effect on the rheological properties and phase separation process of the casting solution. Different solvents will lead to different double diffusion speeds and phase separation mechanisms, thereby affecting the formation of the membrane pore structure. For the polymer and nanofiber in the present invention, the performance of the membrane obtained by selecting the above liquid phase components is better.

[0017] Further preferably, the mass ratio of the solid phase component to the liquid phase component is 0.3 to 1:1.

[0018] In some embodiments of the present invention, the diameter of the hollow fiber nitrogen-rich separation membrane is 0.25-0.33 mm, and the wall thickness is 0.06-0.09 mm.

[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane.

[0020] The preparation method provided by the present invention comprises the steps of preparing a casting solution, spinning and film solidification; wherein the preparation of the casting solution comprises: mixing an organic polymer, a pore-forming agent and a liquid phase component, and then mixing the obtained material with nanofibers.

[0021] Further preferably, in the step of mixing the obtained material with the nanofibers, the mixing time is t, the mixing temperature is T, and the following conditions are satisfied: t = X - (L / D) 1 / 2 Hours, T = X + (L / D) 1 / 2 ℃, the value range of X is 50~60.

[0022] In a third aspect, the present invention provides the use of the above hollow fiber nitrogen-rich separation membrane in separating gases, for example, in separating a mixed gas of oxygen and nitrogen.

[0023] The present invention provides a hollow fiber nitrogen-rich separation membrane and a preparation method and application thereof. The hollow fiber nitrogen-rich separation membrane prepared by reasonable matching of casting liquid components has the advantages of high mechanical strength, good air permeability and high pressure resistance, and has good permeability and selectivity when used in oxygen / nitrogen separation process. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope image of the cross section of the hollow fiber membrane prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0027] If not otherwise specified, the diameter described in the present invention refers to the outer diameter.

[0028] Example 1

[0029] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0030] Solid phase components:

[0031] Organic polymer: polysulfone (number average molecular weight Mw is 50000) and sulfonated polysulfone (number average molecular weight Mw is 50000, sulfonation degree is 10%) in a mass ratio of 5:1; the mass percentage is 94.9%;

[0032] Pore-forming agent: polyethylene glycol, mass percentage is 0.1%;

[0033] Nanofiber: Kevlar fiber, diameter D = 5nm, length L = 5000nm; mass percentage is 5%;

[0034] Liquid phase components:

[0035] A mixture of N,N-dimethylacetamide and water, with a mass ratio of 10:1.

[0036] The mass ratio of the solid phase component to the liquid phase component is 0.3:1.

[0037] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0038] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 18 hours, mixing temperature is 92° C.), and vacuum degassing is performed to obtain a casting solution;

[0039] The casting liquid is extruded from the spinneret at an extrusion pressure of 0.6 MPa, wherein the core liquid is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the core liquid temperature is 35°C, and the core liquid pressure is 0.04 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 12 cm, the coagulation bath is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the temperature is 65°C, and the coagulation bath depth is 45 cm;

[0040] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0041] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.25 mm and a wall thickness of 0.06 mm.

[0042] Example 2

[0043] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0044] Solid phase components:

[0045] Organic polymer: polysulfone (number average molecular weight: Mw 80,000) and sulfonated polysulfone (number average molecular weight: Mw 80,000, degree of sulfonation: 30%) in a mass ratio of 10:1; mass percentage: 89.7%;

[0046] Pore-forming agent: polyethylene glycol, mass percentage is 0.3%;

[0047] Nanofiber: cotton fiber, diameter D = 50nm, length L = 500nm; mass percentage is 10%;

[0048] Liquid phase components:

[0049] A mixture of dimethyl sulfoxide and water, with the mass ratio of each component being 20:1.

[0050] The mass ratio of the solid phase component to the liquid phase component is 1:1.

[0051] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0052] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 47 hours, mixing temperature is 63° C.), and vacuum degassing is performed to obtain a casting solution;

[0053] The casting liquid is extruded from the spinneret at an extrusion pressure of 0.8 MPa, wherein the core liquid is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the core liquid temperature is 30°C, and the core liquid pressure is 0.03 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 15 cm, the coagulation bath is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the temperature is 70°C, and the coagulation bath depth is 45 cm;

[0054] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0055] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.33 mm and a wall thickness of 0.09 mm. The cross-sectional scanning electron microscope image thereof is shown in FIG. Figure 1 shown.

[0056] Example 3

[0057] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0058] Solid phase components:

[0059] Organic polymer: polysulfone (number average molecular weight: Mw 65000) and sulfonated polysulfone (number average molecular weight: Mw 65000, degree of sulfonation: 20%) in a mass ratio of 15:1; mass percentage: 89.5%;

[0060] Pore-forming agent: polyvinyl pyrrolidone, mass percentage is 0.5%;

[0061] Nanofiber: carbon fiber, diameter D = 20nm, length L = 3000nm; mass percentage is 10%;

[0062] Liquid phase components:

[0063] A mixture of N,N-dimethylformamide and water, with the mass ratio of each component being 15:1.

[0064] The mass ratio of the solid phase component to the liquid phase component is 0.5:1.

[0065] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0066] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 38 hours, mixing temperature is 72° C.), and vacuum degassing is performed to obtain a casting solution;

[0067] The casting liquid is extruded from the spinneret at an extrusion pressure of 1 MPa, wherein the core liquid is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the core liquid temperature is 40°C, and the core liquid pressure is 0.05 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 20 cm, the coagulation bath is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the temperature is 75°C, and the coagulation bath depth is 60 cm;

[0068] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0069] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.3 mm and a wall thickness of 0.08 mm.

[0070] Example 4

[0071] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0072] Solid phase components:

[0073] Organic polymer: polysulfone (number average molecular weight: Mw 75000) and sulfonated polysulfone (number average molecular weight: Mw 75000, degree of sulfonation: 25%) in a mass ratio of 20:1; mass percentage: 84.6%;

[0074] Pore-forming agent: polyethylene glycol, mass percentage is 0.4%;

[0075] Nanofiber: bacterial cellulose, diameter D = 10nm, length L = 2000nm; mass percentage is 15%;

[0076] Liquid phase components:

[0077] A mixture of N,N-dimethylacetamide and water, with the mass ratio of each component being 18:1.

[0078] The mass ratio of the solid phase component to the liquid phase component is 0.8:1.

[0079] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0080] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 36 hours, mixing temperature is 74° C.), and vacuum degassing is performed to obtain a casting solution;

[0081] The casting liquid is extruded from the spinneret at an extrusion pressure of 1 MPa, wherein the core liquid is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:1, the core liquid temperature is 45°C, and the core liquid pressure is 0.05 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 20 cm, the coagulation bath is a mixture of water and N,N-dimethylformamide in a volume ratio of 1:1, the temperature is 75°C, and the coagulation bath depth is 80 cm;

[0082] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0083] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.29 mm and a wall thickness of 0.08 mm.

[0084] Example 5

[0085] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0086] Solid phase components:

[0087] Organic polymer: polysulfone (number average molecular weight: Mw 65000) and sulfonated polysulfone (number average molecular weight: Mw 65000, degree of sulfonation: 20%) in a mass ratio of 15:1; mass percentage: 89.5%;

[0088] Pore-forming agent: polyvinyl pyrrolidone, mass percentage is 0.5%;

[0089] Nanofiber: carbon fiber, diameter D = 100nm, length L = 500nm; mass percentage is 10%;

[0090] Liquid phase components:

[0091] A mixture of N,N-dimethylformamide and water, with the mass ratio of each component being 15:1.

[0092] The mass ratio of the solid phase component to the liquid phase component is 0.5:1.

[0093] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0094] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 47 hours, mixing temperature is 62° C.), and vacuum degassing is performed to obtain a casting solution;

[0095] The casting liquid is extruded from the spinneret at an extrusion pressure of 1 MPa, wherein the core liquid is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the core liquid temperature is 40°C, and the core liquid pressure is 0.05 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 20 cm, the coagulation bath is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the temperature is 75°C, and the coagulation bath depth is 60 cm;

[0096] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0097] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.31 mm and a wall thickness of 0.085 mm.

[0098] Example 6

[0099] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0100] Solid phase components:

[0101] Organic polymer: polysulfone (number average molecular weight: Mw 25000) and sulfonated polysulfone (number average molecular weight: Mw 25000, degree of sulfonation: 5%) in a mass ratio of 15:1; mass percentage: 89.5%;

[0102] Pore-forming agent: polyvinyl pyrrolidone, mass percentage is 0.5%;

[0103] Nanofiber: carbon fiber, diameter D = 20nm, length L = 3000nm; mass percentage is 10%;

[0104] Liquid phase components:

[0105] A mixture of N,N-dimethylformamide and water, with the mass ratio of each component being 15:1.

[0106] The mass ratio of the solid phase component to the liquid phase component is 0.5:1.

[0107] The preparation method is the same as that in Example 3.

[0108] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.32 mm and a wall thickness of 0.075 mm.

[0109] Example 7

[0110] This embodiment provides a hollow fiber nitrogen-rich separation membrane, and the composition of the membrane casting solution is as follows:

[0111] Solid phase components:

[0112] Organic polymer: polysulfone (number average molecular weight: Mw 65000) and sulfonated polysulfone (number average molecular weight: Mw 65000, degree of sulfonation: 20%) in a mass ratio of 15:1; mass percentage: 89.5%;

[0113] Pore-forming agent: polyvinyl pyrrolidone, mass percentage is 0.5%;

[0114] Nanofiber: carbon fiber, diameter D = 20nm, length L = 3000nm; mass percentage is 10%;

[0115] Liquid phase components:

[0116] A mixture of N,N-dimethylformamide and water, with the mass ratio of each component being 15:1.

[0117] The mass ratio of the solid phase component to the liquid phase component is 0.5:1.

[0118] This embodiment also provides a method for preparing the above-mentioned hollow fiber nitrogen-rich separation membrane, comprising the following steps:

[0119] After mixing the organic polymer, the pore-forming agent and the liquid phase component, the obtained material is mixed with the nanofiber (mixing time is 10 hours, mixing temperature is 50° C.), and vacuum degassing is performed to obtain a casting solution;

[0120] The casting liquid is extruded from the spinneret at an extrusion pressure of 1 MPa, wherein the core liquid is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the core liquid temperature is 40°C, and the core liquid pressure is 0.05 MPa; after passing through an air layer and a coagulation bath, the hollow fiber membrane is solidified, wherein the air gap is 20 cm, the coagulation bath is a mixture of water and N,N-dimethylacetamide in a volume ratio of 1:1, the temperature is 75°C, and the coagulation bath depth is 60 cm;

[0121] The prepared hollow fiber membrane was immersed in deionized water for 48 hours, during which the deionized water was replaced twice, and then dried to obtain the hollow fiber membrane that can be used for air separation and nitrogen enrichment.

[0122] The hollow fiber nitrogen-rich separation membrane prepared in this example has a diameter of 0.28 mm and a wall thickness of 0.083 mm.

[0123] Comparative Example 1

[0124] This comparative example provides a hollow fiber nitrogen-enriched separation membrane, and the composition of the membrane casting solution is as follows:

[0125] Solid phase components:

[0126] Organic polymer: polysulfone, mass percentage is 94.9%;

[0127] Pore-forming agent: polyethylene glycol, mass percentage is 0.1%;

[0128] Nanofiber: Kevlar fiber, diameter D = 5nm, length L = 5000nm; mass percentage is 5%;

[0129] Liquid phase components:

[0130] A mixture of N,N-dimethylacetamide and water, with the mass ratio of each component being 10:1.

[0131] The mass ratio of the solid phase component to the liquid phase component is 0.3:1.

[0132] The preparation method is the same as that of Example 1.

[0133] Comparative Example 2

[0134] This comparative example provides a hollow fiber nitrogen-enriched separation membrane, and the composition of the membrane casting solution is as follows:

[0135] Solid phase components:

[0136] Organic polymer: polysulfone (number average molecular weight: Mw 65000) and sulfonated polysulfone (number average molecular weight: Mw 65000, degree of sulfonation: 20%) in a mass ratio of 15:1; mass percentage: 99.5%;

[0137] Pore-forming agent: polyvinyl pyrrolidone, with a mass percentage of 0.5%.

[0138] Liquid phase components:

[0139] A mixture of N,N-dimethylformamide and water, with the mass ratio of each component being 15:1.

[0140] The mass ratio of the solid phase component to the liquid phase component is 0.5:1.

[0141] The preparation method is the same as that in Example 3.

[0142] Performance Testing

[0143] The hollow fiber nitrogen-rich separation membranes obtained in the examples and comparative examples were tested for gas permeability, mechanical strength and pressure resistance.

[0144] The test method is as follows:

[0145] Gas separation performance: The prepared hollow fiber membrane was sealed with epoxy resin, and the gas separation performance was tested using gas chromatography.

[0146] Pressure resistance test: seal one end of the prepared hollow fiber membrane and pass high-pressure gas into the other end to test the pressure resistance performance. When the membrane can maintain a certain pressure for 30 minutes without damage, the pressure at this time is determined as the pressure resistance.

[0147] Mechanical strength test: The prepared hollow fiber membrane was cut into a certain length and subjected to a mechanical tensile performance test using a universal testing machine.

[0148] The test results are shown in Table 1 below.

[0149] Table 1

[0150]

[0151] From the above results, it can be seen that the polymer of the present invention selects polysulfone and sulfonated polysulfone composed of a specific ratio, which is helpful for enriching nitrogen. Comparative Example 1 only uses polymer polysulfone, and the oxygen / nitrogen selectivity is poor. The sulfonation degree of the sulfonated polysulfone selected in Example 6 is not 10-30%, and the effect is worse than that of Example 3. At the same time, the present invention adds nanofibers, which helps to improve the mechanical strength of the membrane while maintaining permeability, and has strong bendability during processing. Comparative Example 2 does not add nanofibers, and the tensile properties, fracture percentage and compressive resistance are poor. Further, the diameter D and length L of the nanofibers meet: 5nm≤D≤50nm, 500nm≤L≤5000nm, the effect is better, and Example 5 does not meet it, which is worse than Example 3; further, preferably 100≤L / D≤200, Examples 3 and 4 meet this condition, and the effect is better than Examples 1 and 2 that do not meet this condition. In the process of mixing the nanofibers with the organic polymer, the pore former and the liquid phase component in Example 7, the mixing time t and the mixing temperature T do not meet the preferred conditions found by the present invention, and the effect is worse than that of Example 3.

[0152] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0153] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementations", or "some specific implementations" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A hollow fiber nitrogen-enriched separation membrane, characterized in that: The casting solution of the hollow fiber nitrogen-rich separation membrane comprises a liquid phase component and a solid phase component, wherein the solid phase component comprises an organic polymer, a pore former and nanofibers; the organic polymer is composed of polysulfone and sulfonated polysulfone in a mass ratio of 5 to 20:1; the mass proportion of the pore former in the solid phase component is 0.1% to 0.5%; the mass proportion of the nanofiber in the solid phase component is 5% to 15%; The nanofiber is selected from one or more of Kevlar fiber, cotton fiber, carbon fiber, and bacterial cellulose; The diameter of the nanofiber is D, and the length is L, which respectively satisfy: 5nm≤D≤50nm, 500nm≤L≤5000nm; The diameter D and length L of the nanofiber also satisfy: 100≤L / D≤200; The number average molecular weight of the polysulfone is 50,000 to 80,000; The number average molecular weight of the sulfonated polysulfone is 50,000-80,000, and the sulfonation degree is 10-30%.

2. The hollow fiber nitrogen-rich separation membrane according to claim 1, characterized in that: The pore-forming agent is selected from one or more of polyethylene glycol and polyvinyl pyrrolidone.

3. The hollow fiber nitrogen-enriched separation membrane according to claim 1 or 2, characterized in that: The liquid phase component is a mixture of one or more of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and water; The mass ratio of the solid phase component to the liquid phase component is 0.3 to 1:

1.

4. The hollow fiber nitrogen-enriched separation membrane according to claim 1 or 2, characterized in that: The outer diameter of the hollow fiber nitrogen-rich separation membrane is 0.25-0.33 mm, and the wall thickness is 0.06-0.09 mm.

5. The method for preparing a hollow fiber nitrogen-rich separation membrane according to any one of claims 1 to 4, characterized in that: The method comprises the steps of preparing a casting solution, spinning the film and solidifying the film; The preparation of the casting solution includes: mixing the organic polymer, the pore-forming agent and the liquid phase component, and then mixing the obtained material with the nanofiber.

6. The method for preparing a hollow fiber nitrogen-rich separation membrane according to claim 5, characterized in that: In the step of mixing the obtained material with the nanofibers, the mixing time is t, the mixing temperature is T, and the following conditions are satisfied: t = X - (L / D) 1 / 2 Hours, T = X + (L / D) 1 / 2 ℃, the value range of X is 50~60.

7. Use of the hollow fiber nitrogen-rich separation membrane according to any one of claims 1 to 4 in separating gases.

Citation Information

Patent Citations

  • Preparation method of nanocellulose composite polysulfone hollow fiber membrane

    CN105664740A

  • Method for preparing novel long-lasting hydrophilic polysulfone ultrafiltration membrane

    CN107754618A

  • Hollow fiber oxygen separation membrane and method for preparing same

    CN1876222A